The Effect of Using Information Gap Technique to Improve Students’ Speaking Skill in The EFL Context - Triana, Neni; Anita, Fenny (Tamaddun Life, 2022)
Using information gap technique in teaching speaking is a way where the pupil is lacking a few information important to finish a task or resolve a trouble, and they should communicate with their classmates to fill the gaps. The purpose of this studies turned into to find the effect of the use of the Information gap technique on EFL students’ speaking competencies. the design of this research became the use of experimental research with Pretest and post-test procedures. The pattern of this research become 64 students on first grade students of SMPN 1 Rambah Hilir. They had been divided into two groups, the experimental group, and the manipulate institution. The information was analyzed the usage of the t-test approach to discover the whether or not significant distinction effect between the experimental group become taught the usage of the information gap technique and the control group became taught by the non-information gap technique. The result of this research turned into observed that the students’ speaking skill in each of the groups inside the pretest became the same an average rating of 51.85 and their degrees have been mediocre. After being taught the information gap technique the experimental group had seventy 75 with a degree a good ability and the control group become taught the noninformation technique with average 51.85 or still mediocre ability. It could finish that using the information gap technique can improve the students' speaking skill at SMPN 1 Rambah Hilir in the EFL context. This technique can improve speaking skill for students at SMPN 1 Rambah Hilir.